Sistem Pembuktian Materil dalam Perkara Perdata Waris di Pengadilan Agama Samarinda (Studi Putusan Pengadilan Agama Samarinda Nomor: 850/Pdt.G/2023/PA.Smd) - Dhimas Abbe Pramudya; Lilik Andaryuni (Bulletin of Community Engagement, 2024)
The system of evidence in civil cases only needs to be realized by the judge in the form of formal truth. However, Decision Number: 850/Pdt.G/2023/PA.Smd The Panel of Judges has put aside the principle of formal evidence and used a material evidence system to find the truth in the inheritance case. The aim of this research is to understand the concept of proof in civil cases in Indonesia and analyze the proof system in Decision Number: 850/Pdt.G/2023/PA.Smd. This research is normative research with a statutory and conceptual approach. The results of the study show that inheritance cases are one of the civil cases, where the evidentiary system achieves formal truth. Decision Number: 850/Pdt.G/2023/PA.Smd provides the view that although inheritance is one of the civil cases, it is not necessarily rigid to the civil law evidentiary system which seeks formal truth, but depends on the circumstances and position of the case which requires proof others in seeking the truth of a dispute, one of which is through the testimony of witnesses who are decisive in the judge a quo's considerations.